The Tripeptide RER Mimics Secreted Amyloid Precursor Protein-Alpha in Upregulating LTP - Morrissey, Jodi A.; Bigus, Erin; Necarsulmer, Julie C.; Srinivasan, Vinay; Peppercorn, Katie; O’Leary, Daniel J.; Mockett, Bruce G.; Tate, Warren P.; Hughes, Stephanie M.; Parfitt, Karen D.; Abraham, Wickliffe C. (Frontiers in Cellular Neuroscience, 2019)
Secreted amyloid precursor protein-alpha (sAPPα), generated by enzymatic processing of the amyloid precursor protein, possesses a range of neurotrophic and neuroprotective properties and plays a critical role in the molecular mechanisms of memory and learning. One of the key active regions of sAPPα is the central APP domain (E2) that contains within it the tripeptide sequence, RER. This sequence is exposed on the surface of a coiled coil substructure of E2. RER has by itself displayed memory-enhancing properties, and can protect newly formed engrams from interference in a manner similar to that displayed by sAPPα itself. In order to determine whether RER mimics other properties of sAPPα, we investigated the electrophysiological effects of the N-terminal protected acetylated RER (Ac-RER) and an isoform containing a chiral switch in the first amino acid from an l- to a d-orientation (Ac-rER), on synaptic plasticity. We found that, like sAPPα, exogenous perfusion with nanomolar concentrations of Ac-RER and Ac-rER enhanced the induction and stability of long-term potentiation (LTP) in area CA1 of rat and mouse hippocampal slices, in a protein synthesis- and trafficking-dependent manner. This effect did not occur with a control Ac-AAA or Ac-IFR tripeptide, nor with a full-length sAPPα protein where RER was substituted with AAA. Ac-rER also protected LTP against amyloid-beta (Aβ25-35)-induced LTP impairment. Our findings provide further evidence that the RER-containing region of sAPPα is functionally significant and by itself can produce effects similar to those displayed by full length sAPPα, suggesting that this tripeptide, like sAPPα, may have therapeutic potential.